New analytical approach to nonlinear behavior study of asymmetrically LCBs on nonlinear elastic foundation under steady axial and thermal loading - H. Rafieipour; A. Lotfavar; M. H. Mansoori (Latin American Journal of Solids and Structures)
In this paper, nonlinear behavior analysis of an asymmetrically laminated composite beam (LCB) on nonlinear foundation under axial and in-plane thermal loading is considered. To solve the obtained governing equation, a novel method based on Laplace transform is used. The resulted approximate analytical solution allows us the parametric study of different parameters which influence the nonlinear behavior of the system. The numerical results illustrate that proposed technique yields a very rapid convergence of the solution as well as low computational effort. The accuracy of the proposed method is verified by those available in literatures.